MENINGKATKAN KREATIFITAS ANAK USIA DINI MELALUI PEMBELAJARAN BERDIFERENSIASI - Solekah; Arri Handayani; Dini Rahmawati (STKIP Subang, 2023)
Early Childhood Education (PAUD) is a critical stage in establishing the basis for child development, including aspects of creativity. This research aims to present a literature review that explores how differentiated learning approaches can be used to increase children's creativity at the PAUD level. Involving analysis of various literary sources such as journals, books and articles, this research explores the strategies and impact of differentiated learning on the creative development of early childhood. The problem in the field is that many schools still use conventional methods where children just sit, be quiet and listen, thereby limiting children's creativity. Children will be said to be smart when they silently follow all of the teacher's instructions, so through this article the author wants to convey how to make children more creative through differentiated learning